PRYWATNOŚĆ JAKO OKOLICZNOŚĆ OGRANICZAJĄCA SWOBODĘ WYPOWIEDZI NA TEMAT OSOBY FIZYCZNEJ. ASPEKT PRAWNY - Tylec, Grzegorz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article discussed legal regulations concerning protection of the right to privacy, which may constitute a barrier to the free dissemination information about persons in the press. It was discussed the general principle - freedom of expression and its limitations which is right to privacy. The analysis concerns the extent of the interference in the privacy due to social functions that a person performs in society and due to interest person causes in public life. In the article it was pointed how the terms: “public activity”, “public person”, “public officer” were defined in judicature and doctrine of the law. In a broad way it was discussed art. 14 paragraph 6 of the polish press law which concerns interference with the right to privacy.